Haemophilia A: Pharmacoeconomic Review of Prophylaxis Treatment versus On-Demand - Brigid Unim; Maria Assunta Veneziano; Antonio Boccia; Walter Ricciardi; Giuseppe La Torre (The Scientific World Journal)
Objectives. Haemophilia A is a congenital disorder of coagulation that mainly affects males and causes a considerable use of resources, especially when hemophilic patients are treated with prophylaxis. The aim of the present review was to discuss and appraise the methodological aspects and results of published economic evaluations of haemophilia A treatments in the last decade. Methods. The literature search, performed by consulting four engines, covered studies published between 2002 and 2014. Full economic evaluations published in English language were identified and included in the review. A quality assessment of the studies was also carried out based on Drummond’s checklist. Results. After careful evaluations of the identified records, 5 studies were reviewed. Primary and secondary prophylaxis resulted cost-effective compared to on-demand therapy: the ICER of primary prophylaxis ranged from €40.236 to €59.315/QALY gained, while the ICER of secondary prophylaxis was €40.229/QALY gained. Furthermore, 60% were high quality and 40% were medium quality studies. Conclusions. The review underlines the cost-effectiveness of prophylaxis versus on-demand treatment and the different methodological approaches applied. Further economic evaluations are required with models that reflect the clinical reality and consumption of resources in each country.